Technical and Economic Efficiency of Smallholder Arabica Coffee Farming in Panti Sub-district, Jember - Dani Widjaya; Yuli Hariyati; Djoko Soejono (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2017)
Many factors must be considered in coffee production processes. Use of factors of production must also be efficient in order to produce maximum production.This research was conducted in Panti Sub-district, Jember, as one of larger coffee producer in Jember. This location was also one area in Jember cultivated with Arabica coffee since 2012. Therefore, this study aimed to determine production factors in Arabica coffee smallholders; particularly technical and economic efficiency of Arabica coffee smallholders. Research method including interview and secondary data collection was carried out in three farmer groups in Panti Sub-district. Samples included 36 farmers from Surya Tani, Sejahtera Bersama and Taman Putri farmer groups. Analytical methods used were Cobb Douglass as a function of Stochastic Frontier to see the technical efficiency of farming and analysis of economic the selected efficiency with pricing approach. Technical efficiency in Arabica coffee farming in the selected locations were considered efficient in the level of 71.4% with aminimum of technical efficiency of 24.9% and a maximum efficiency of 93.4%. Economic efficiency showed that factors of labor and use of organic fertilizers were not efficient, thus there should be a reduction in use of labor and organic fertilizers. The factors indicated also that use of inorganic fertilizers was not efficient, with economic efficiency value (NPM/Px) of 1.579. The conditions indicate that there is a need to use of inorganic fertilizers to be an economically efficient manner.